Inner-Shell Ionization Cross Section of Gold by Electron and Positron Impact (Journal of Atomic and Molecular Sciences, 2021)
The theoretical modified Khare (BEB) model has been used to calculate thetotal cross sections for $L_1,$ $L_2$ and $L_3$-subshells ionization of gold atom due to electronand positron impact for projectile energy varying from the threshold of ionization to 60times the threshold energy For $L$ subshells the present cross section due to electron andpositron impact cross sections are in remarkable agreement with available experimentaldata and other theoretical cross sections. Total $L$ shell ionization cross sections havebeen also calculated in the energy varying from the threshold of ionization to severalMeV by electron impact. It is found good agreement with available experimental data.The investigation for other atoms is in progress.
Keywords: atomic ionization; electron impact; positron impact.